Geological evaluation and favorable area optimization for underground coal gasification in Zhalainuoer coal field - Yi CUI; Shu TAO; Zhiheng WANG; Yaning WU; Qinghe JING; Shoujun LI; Dejun LI; Jie GUO; Shouqing YAN; Yang JIAO; Di ZOU (Meitan xuebao)
Underground coal gasification (UCG) can control the combustion of in-situ coal seams underground to obtain combustible synthesis gas, which is expected to become an important way to fill the gap in natural gas supply and demand in China. The site selection for UCG requires comprehensive consideration of various factors such as coal’s own characteristics and the geological environment of coal seams. Objective site selection evaluation is the basic guarantee for the stable operation of UCG. On the basis of identifying the geological conditions of the Zhalainuoer coal field, the feasibility of UCG and the favorable areas for UCG of the main coal seam in the Yimin Formation are comprehensively analyzed from four aspects: coal petrological and quality characteristics, coal occurrence conditions, structural conditions, and hydrogeological conditions. Moreover, Analytic Hierarchy Process (AHP) and fuzzy mathematics evaluation method are used to develop the multi-level site selection evaluation system, which comprises 4 primary indicators and 13 secondary indicators. This evaluation system is used to clarify the distribution characteristics of favorable areas for UCG in the Zhalainuoer coal field. The results show that Ⅱ2-1 and Ⅱ3 coal seams of the Yimin Formation are lignite with medium total moisture content, low ash yield, high volatile matter yield. The content of harmful elements such as nitrogen and sulfur in coal is low. The average calorific value (Qnet,ar) of the two coal seams is 23.41 and 23.73 MJ/kg, respectively, and the average gasification activity (CO2，900 ℃) is 91.90% and 79.64%, respectively, and the average value of thermal stability (TS-6) is 58.95% and 58.20%, respectively, and the melting point of coal ash is 1145 and 1170 ℃, respectively. The coal seam has a large thickness and stable lateral distribution (coal thickness variation coefficient of 10.14%～33.55%), with moderate burial depth and low complexity of faults. The average unit water inflow of coal seams is generally low, and the coal bearing strata have well-developed and stable aquitards. Overall, the Ⅱ2-1 and Ⅱ3 coal seams in the Zhalainuoer coal field have the feasibility of implementing UCG tests. The southern part of Lingdong Coal Mine is identified as a class I favorable area for UCG in the II2-1 coal seam. Meanwhile, the Lingdong Coal Mine, the southern part of Lingdong Coal Mine and the Lingquan Coal Mine are identified as class I favorable areas for UCG in the II3 coal seam. It is suggested to further carry out physical simulation experiments on UCG in favorable areas to obtain key parameters such as gasification products and gasification efficiency, to implement gasification furnace construction plans, and to optimize gasification processes.